Elastic-plastic numerical analysis of tensile specimens with surface center-cracked asymmetric welded x-joint - E. Doncheva, B.Medj, G.Adziev, S.Sedmak (Faculty of Mechanical Engineering, University of Belgrade, 2015)
The aim of this work is to determine appropriate numerical model to simulate the experimental evaluation of fracture resistance properties of tensile panels with surface crack located in the central section of asymmetric X-joint. The investigation is performed on high-strength low alloyed (HSLA) steel with undermetched weld configuration. Numerical analysis was carried out by ABAQUS three dimensional elastic plastic analysis mode. The work was performed on centre-cracked welded specimens, with two different sized cracks in order to examine the geometry impact on fracture resistance parameters. Comparison between experimental and numerically obtained results is done with attention focused on J-integral, crack mouth opening displacement (CMOD) and J-R resistant curves. Results are discussed in terms of further development on modeling procedure and technique. Approaching to real fracture behavior in similar welded structures with numerical investigation, can be far more economical solution instead of performing experiments. This paper, shows that simulations are promising in respect to their accuracy and can be used as a toll for further development of numerical models that have more complex nature.
Keywords: welded joint, surface crack, heterogeneity, mismatch